Obtenção de nanocompósitos magnéticos de Fe3O4-talco sintético com matrizes poliuretânicas base solvente e base água - Santos, Leonardo Moreira dos (2017)
The obtaining of materials with different and superior properties when compared to existing materials is one of the main research focuses in polymeric materials field. Nanocomposites are important in this sector because they combine materials with good performance in order to obtain new features that can be used in different niches in the market. Polyurethane based materials finds a wide application and is widely used in industry. The insertion of an alternative inorganic filler is often used to obtain better properties of these polymeric materials. Thus, this work aims to incorporate different proportions of a new filler Fe3O4-synthetic talc, in powder and gel form, in solvent and waterborne polyurethane matrix. Nanocomposites PU solvent/ Fe3O4-synthetic talc obtained by physical mixture presented a good filler dispersion/exfoliation even at higher filler contents of 10% as corroborated by XRD and TEM techniques. Mössbauer and magnetic measurements confirmed the magnetic behavior of nanocomposites, being ferromagnetic in all tested temperatures. The use of synthetic talc to obtain magnetic nanocomposites produced materials with higher crystallization temperature and thermal stability compared with the polymeric matrix. This method is efficient to avoid attracting dipolar magnetite and therefore the charge aggregation. Nanocomposites WPU/ Fe3O4-synthetic talc presented better mechanical properties with higher filler contents compared to the pure polymer. The XRD analysis evidenced a formation of an intercalated structure between the polymer matrix and nanoparticles. Nuclear Magnetic Resonance (NMR) measurements evidenced the interaction filler/WPU corroborating the AFM analyses. Mössbauer and magnetization curves highlighted that the magnetic properties are temperature dependent unlike for nanocomposites obtained with solvent based PU.